Differences in the Clinical Characteristics and 1-Year Mortality Rates of Patients with Dermatomyositis with anti-Jo-1 and anti-MDA5 Antibodies - Chao-Han Liu; Chew-Teng Kor; Ming-Hui Hung; Kai-Hung Hsiao; Yen-Huang Cheng; Ya-Chih Tien (Journal of Immunology Research)
Objective. Patients with anti-Jo-1 antibodies (Abs) and anti–melanoma differentiation-associated protein 5 (MDA5) Abs are at a higher risk of interstitial lung disease (ILD) and have a mortality rate higher than that of patients with anti-Jo-1 Abs. This study investigated differences in the clinical characteristics and prognosis of patients with anti-Jo-1 Abs and anti-MDA5 Abs with dermatomyositis (DM). Methods. We retrospectively reviewed the medical records of 38 patients with DM from January 2000 to December 2021. The patients were divided into anti-Jo-1 Abs and anti-MDA5 Abs groups. The basic demographic data, clinical manifestations, and 1-year mortality rates of the groups were compared. Results. Among the 38 patients, 30 were anti-Jo-1-Abs positive and 8 patients were anti-MDA5 Aba positive. The patients with anti-MDA5 Abs presented with more apparent cutaneous symptoms and aggressive pulmonary manifestations than did those with anti-Jo-1 Abs. The mortality rate in the anti-MDA5 Abs group (1.95/person-year (PY)) was much higher than that in anti-Jo-1 Abs group (0.094/PY), and most of the mortalities occurred within the first 1–3 months of follow-up. Conclusion. Distinct cutaneous and pulmonary manifestations were observed in the anti-Jo-1 Abs and anti-MDA5 Abs groups. The mortality rate in the anti-MDA5 Abs group was significantly higher than that in the anti-Jo-1 Abs group. Early recognition is crucial to ensuring higher chances of survival for patients with anti-MDA5 Abs.